Targeted bisulfite sequencing of the dynamic DNA methylome. Issue 1 (December 2016) - Ziller, Michael; Stamenova, Elena; Gu, Hongcang; Gnirke, Andreas; Meissner, Alexander
Abstract Background The ability to measure DNA methylation precisely and efficiently continues to drive our understanding of this modification in development and disease. Whole genome bisulfite sequencing has the advantage of theoretically capturing all cytosines in the genome at single-nucleotide resolution, but it has a number of significant practical drawbacks that become amplified with increasing sample numbers. All other technologies capture only a fraction of the cytosines that show dynamic regulation across cell and tissue types. Results Here, we present a novel hybrid selection design focusing on loci with dynamic methylation that captures a large number of differentially methylated gene-regulatory elements. We benchmarked this assay against matched whole genome data and profiled 25 human tissue samples to explore its ability to detect differentially methylated regions. Conclusions Our target capture design fills a major gap left by all other assays that exist to map DNA methylation. It maintains the ability to link cytosine methylation to genetic differences, the single-base resolution and the analysis of neighboring cytosines while notably reducing the cost per sample by focusing the sequencing effort on the most informative and relevant regions of the genome.